Conflict and agricultural productivity: Evidence from Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Evidence is scarce on how conflict affects technology adoption and consequent agricultural productivity in fragile states, an important topic given the high share of the extreme poor living in fragile environments globally. Our study contributes to filling this knowledge gap by using unique large-scale data on rice producers in Myanmar before and after a military coup in 2021, leading to a surge of conflicts in the country. We find that the increase in violent events significantly changed rice productivity. Specifically, increases in fatal violent events between 2020 and 2021 reduced rice Total Factor Productivity (TFP) – a measure of how efficiently agricultural inputs are used to produce rice – by about 4 percent on average in the short-run. Moreover, poorer farmers are more affected by conflict, as seen through an increased output elasticity to agricultural equipment owned, indicating reduced output resilience for less-capital owning, and therefore poorer, farmers. This seems partly due to reduced access to agricultural extension services, which would otherwise help farmers maintain productivity, even with limited capital ownership, through substitution with human capital and skills. Lower mechanization service fees partly mitigate these effects. Our results consistently hold for both short- and long-run production functions, across various specifications, and in Upper and Lower Myanmar. These findings suggest that containing and reducing violent events is critical in restoring rice productivity. Improved access to extension services, as well as to cheap mechanization service provision to mitigate lack of equipment ownership, could compensate for these losses and boost the productivity of farmers, especially for those with less production capital, in such fragile settings.